Management of traumatic dental injuries: a survey of paediatric emergency department health professionals. Issue 1 (22nd March 2023) - Gallichan, Nathalie; Albadri, Sondos; Watkins, Francine; Jarad, Fadi; Messahel, Shrouk; Hartshorn, Stuart; Gartshore, Laura
Abstract : Objective: To assess paediatric emergency department (PED) health professionals' confidence, experience and awareness in managing traumatic dental injuries (TDIs). Design: A cross-sectional online survey. Setting: PED at Alder Hey Children's Hospital and Birmingham Children's Hospital. Results: 94 ED health professionals responded. One-third of responders (n=26) encounter children with dental trauma daily or weekly. TDI teaching during undergraduate training was received by 13% (n=12) of responders, and 32% (n=30) had never received training. Responders thought they would benefit from online resources and regular teaching on paediatric TDIs, in addition to an easy-to-use decision-making tool to signpost families. ED health professionals' confidence in giving advice to families following a TDI, and in recognising types of TDIs, was notably low; −79 and −76 Net Promotor Score, respectively. Responders' awareness of how to recognise and manage TDIs was varied. Majority were aware of the need to attempt to reimplant an avulsed permanent tooth, and the need to refer a child presenting with a complex permanent tooth injury to the oncall dentist. However, very few responders commented on the importance of follow-up. Responders also raised concerns about the lack of dental services to treat TDIs in children. Conclusions: There is a need to enhance dental trauma teaching for all ED health professionals who encounter TDIs to increase their confidence and enable them to triage and advise patients appropriately. Additionally, increased signposting for families to the appropriate service could in turn improve outcomes and experience for children who experience a TDI.